2018
DOI: 10.1177/0014402918787339
|View full text |Cite
|
Sign up to set email alerts
|

Skill Moderators of the Effects of a Reading Comprehension Intervention

Abstract: This study utilized secondary analyses of a randomized controlled trial and investigated the extent to which prestest word identification efficiency, reading fluency, and vocabulary knowledge moderated the effects of an intervention on reading comprehension outcomes for struggling readers in sixth through eighth grades. Given that the experimental intervention included components that targeted word reading, reading fluency, and vocabulary, we hypothesized that students with lower pretest performance in those s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 48 publications
2
36
0
1
Order By: Relevance
“…Coyne et al (2019), for example, found that kindergarten students with higher initial vocabulary knowledge reaped greater benefit from a Tier 2 vocabulary intervention than their peers with lower preintervention vocabulary knowledge. Conversely, results from Clemens et al (2019) suggested that students with lower oral reading fluency at pretest made stronger gains in reading comprehension than students with higher pretest reading fluency. Clemens et al (2019), however, found no evidence that initial word identification efficiency or vocabulary knowledge moderated the treatment effects.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Coyne et al (2019), for example, found that kindergarten students with higher initial vocabulary knowledge reaped greater benefit from a Tier 2 vocabulary intervention than their peers with lower preintervention vocabulary knowledge. Conversely, results from Clemens et al (2019) suggested that students with lower oral reading fluency at pretest made stronger gains in reading comprehension than students with higher pretest reading fluency. Clemens et al (2019), however, found no evidence that initial word identification efficiency or vocabulary knowledge moderated the treatment effects.…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, results from Clemens et al (2019) suggested that students with lower oral reading fluency at pretest made stronger gains in reading comprehension than students with higher pretest reading fluency. Clemens et al (2019), however, found no evidence that initial word identification efficiency or vocabulary knowledge moderated the treatment effects. Similarly, L.…”
Section: Discussionmentioning
confidence: 83%
“…However, not all students will respond adequately to instruction (McMaster et al, 2005 ; Fuchs et al, 2014 ), including inferential reading comprehension interventions. In attempts to understand why students respond differently to reading interventions, researchers have increasingly utilized moderation analysis to statistically identify characteristics associated with differential response to reading interventions (e.g., Clemens et al, 2019 ; Miciak et al, 2014 , Vaughn et al, 2019 ). There are many potential characteristics that could moderate students’ response to intervention.…”
Section: Inferential Reading Comprehensionmentioning
confidence: 99%
“…Coyne et al (2019) and Vaughn et al (2019) determined that stronger initial reading and language skills predicted a more positive response. However, Clemens et al (2019) and D. Fuchs et al (2019) obtained an opposite result: Weaker initial skills predicted more positive responses.…”
Section: Predictors Of Responsementioning
confidence: 83%
“…Several research groups have found domain-specific skills (e.g., decoding) predictive of intervention response (Clemens et al, 2019; Coyne et al, 2019; D. Fuchs et al, 2019; Nelson et al, 2003; Scarborough, 1998; Vaughn et al, 2019).…”
Section: Predictors Of Responsementioning
confidence: 99%